Mothers susceptible to child maltreatment and requiring public health nurses' continuous support. Issue 1 (9th November 2021) - Yoshioka‐Maeda, Kyoko; Fujii, Hitoshi
Abstract: Objective: This study aimed to identify the characteristics of mothers who are at a high risk for future child maltreatment and therefore, require continuous support from public health nurses (PHNs) to prevent child maltreatment and those who do not require it. Design and samples: This retrospective cross‐sectional study included women who were registered in 2018 for being at risk for future child maltreatment and required help with childrearing in City A within the Tokyo metropolis. Measurements: Public health nurses registered data pertaining to each mother, including demographic data, family‐related variables, assessment by PHNs, use of maternal and child healthcare services, and continuity of support from PHNs. Results: Of the 206 cases, the discontinued group—comprising those who no longer needed PHNs' support—included 83 cases (40.3%) and the continuing group—comprising those needed continuing support—included 123 cases (59.7%). Logistic regression analysis showed that those with marital conflicts, maternal mental instability, lack of parenting skills, and not moving out of the city were more likely to require continuous PHNs' support. Conclusions: By identifying these factors, PHNs can identify new mothers who need continuous support and provide more concentrated care for them. Thus, support from PHNs can help prevent child maltreatment.